Doing Age and Doing Desire in and Through Film. Queer Perspectives on Gender, Aging, and Desire - Eckert, Lena; Martin, Silke (Frontiers in Sociology, 2018)
In recent years a growing number of films on and with elderly people have been produced. Love and desire are central features of some of these films although more often heterosexual than homosexual. In our paper we would like to address the intersections of doing age and doing desire in five films that have recently been produced. By analysing the films we will develop a taxonomy of the various forms of desire displayed. Yet, we will also show how these films do not just represent desire in old age but how they materialize in and through the desire they produce in us, the spectators. In our analysis we look especially at filmic strategies, which cope with, reify, produce and counter images of desire in old age. We consider these filmic strategies as performative, which means that film can contain a utopian as well as subversive potential. We are especially interested in the potential of film to create something other than expected, something that leads us beyond representation of the known, something new that emerges with the specific aesthetics of film. In order to trace this potential we draw upon the concept of the surrogate body in the cinema which helps us resituate the notion of embodiment in the actual cinematic experience. In this somatic space of meaning, which our body has become for the film, desire moves in the diegetical and the non-diegetical levels of the film. In the films we will analyse, a specific corporeal-somatic experience becomes possible that lies beyond a simple and normalized heterosexuality in old age. The images create, as we want to suggest an ageing trouble by queering our anticipations and stereotypical expectations – they also materialize as desire in the bodies of the spectators.